The Market Institution and the State in Islamic Economics: From Past to Present and Future - Ersoy, Arif; Altundere, Merve Busra (International Journal of Economics, Management and Accounting, 2017)
The market institution determines mutual cooperation, division of labor and coordination among producers and consumers. Free functioning of the market institution supplies information and knowledge to buyers and sellers thus enabling them to make economic decisions for their transaction according to the purchasing power of buyers and the amount of marketable goods and services. Free market institution enables buyers and sellers to use their resources efficiently. The market institution has played crucial roles in arranging balanced relations among demand and supply. The free market does not deceive buyers and sellers. Obstacles created by the state political or capitalist monopolistic powers prevent the market institution from functioning efficiently in providing the right information to sellers and buyers to establish balance between supply and demand. The free market has paved ways for effective mobilization of human and natural resources, whereas the controlled market either by bureaucratic or capitalist monopolies has hindered economic development by wasting and leaving idle some human and natural resources. Islamic economics emphasizes the crucial role of free market institution in arranging a suitable atmosphere for buyers and sellers to meet at a platform called the market. In Islamic economics, one of the main economic duties of the state is to arrange this suitable atmosphere for free functioning of the market institution. Within the limited framework of this article, we will try to give some brief theoretical information about the role of the state in establishing an atmosphere for free market institution functioning in the economic history of the Muslim world. The main duties of the state concerning the free market institution in our time will be evaluated and discussed according to the main economic principles of Islamic economics.